PERODERMA TASSELUM SP. NOV. (LERNAEOCERIFORMES; COPEPCH5A) PARASITIC ON THE FISH ITOLEPHORUS COMMERSONII LACEPEDE - Bennet, P Sam; Chellam, A (Indian Journal of Fisheries, 2011)
The female of a copepod parasite, Peroderma tasselum sp. nov. parasitic on the fish Stolephorus commersonil is described from Tuticorin, southeast coast <^ India. The species can be distinguished from the only other known species of the genus, P. cylindricum, by the characteristic shape of the trunk.